Muslim impulsive buying behavior via e-commerce in West Java - Deni Lubis; Anisa Az Zahra; Tita Nursyamsiah (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2025)
Indonesia is the world's largest Muslim consumer, COVID-19 contributed to the rapidly growing percentage of Internet users and online shopping as well as the availability of an easy-to-access e-commerce platform that encourages user consumption. The act of consumers spontaneously purchasing products without consideration is known as impulsive buying behavior, even though Islam forbids excessive consumption and waste. As no policy governs consumption, this study is critical in providing a reference for policymakers. This study investigates the factors that influence Muslim consumers' impulsive purchasing behavior when shopping on an e-commerce platform. The findings indicated a significant relationship between religiosity and attitudes. While attitudes, subjective norms, and perceived behavioral control impact impulse buying intentions, intentions significantly influence impulsive buying behavior. To prevent impulsive buying behavior, the government and NGOs must be involved in outreach and education to prevent impulsive buying behavior.